Secondary Attack Rate and Epidemiological Determinants of Secondary High-Risk Contacts of SARS COV-2; Lessons to Learn: A Study from North Gujarat - Parul Sharma; Nitin Solanki; Rakesh Ninama (Medsci Publications, 2020)
Background: Transmission of the SARS CoV-2 disease among secondary contacts is a challenge and must be addressed. Secondary attack rate (SAR) is the probability that an infection occurs among susceptible contact within incubation period. It can be influenced by many factors including personal hygiene habits, behaviors, and characteristics of close-contact environments. Objectives: The study was conducted to finds out the Secondary Attack Rate among Household contacts of Covid19 positive patients; to study the socio-demographic and other factors affecting the Secondary Attack Rate; and to compare the disease outcomes in the primary cases and secondary contacts. Methodology: Observational Retrospective Study was conducted telephonically among randomly selected 444 primary contacts from District Patan and their 1059 secondary high-risk contacts. Results and conclusion: The overall SAR was found to be 5.6% which was highest (21%) in >60 years age group followed by 18 to<60 years age group (5.6%).Death rates were higher(18%) in Primary cases compared to High Risk secondary contacts (8%).Gender, age, symptomatic contacts, presence of toilet facility, Travel History and co-morbid conditions were found to be statistically significant in High Risk secondary contacts. Home isolation seems to be a good measure for Covid 19 positive cases except for those >60 years old.